1989
DOI: 10.1063/1.1140335
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed molecular-beam, diode-laser spectrometry using rapid scanning techniques

Abstract: A novel technique to fabricate GaInAsP/InP buried heterostructure laser diodes Appl. Phys. Lett. 44, 975 (1984); 10.1063/1.94617 Stripe geometry leadtelluride diode lasers grown by molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…cules formed in a supersonic jet, namely optothermal detecObviously, similar interactions may also be expected for tion of a continuous molecular beam (5) and direct absorpthe other noble gases, Ne, Kr, and Xe, with N 2 O. With the tion spectroscopy (6).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…cules formed in a supersonic jet, namely optothermal detecObviously, similar interactions may also be expected for tion of a continuous molecular beam (5) and direct absorpthe other noble gases, Ne, Kr, and Xe, with N 2 O. With the tion spectroscopy (6).…”
Section: Introductionmentioning
confidence: 87%
“…Unlike CO 2 and OCS, the rare gas-N 2 O comis currently aimed at characterizing these interactions by plexes are not well studied, and consequently, there is little forming bimolecular complexes in the gas phase and examininformation available except for Ar-N 2 O. The Ar-N 2 O speing them using spectroscopic techniques (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The Ar-CO complex can be considered a prototype van der Waals system, as witnessed by the extensive experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31] work on its description. For example, the first paper, published in 1978 by Parker and Pack, 20 used Ar-CO as a model system for the development of electron gas methods for calculating intermolecular potential energy surfaces ͑IPESs͒.…”
Section: Introductionmentioning
confidence: 99%
“…The first experimental observation of the Ar-CO complex was done by De Piante et al 1 and the first detailed studies of the infrared spectrum were reported by McKellar et al 2 They were able to assign six b-type transitions ͑with ⌬KϭϮ1) for K values up to 3 in the CO fundamental band. Later Xu et al 7 extended this work to K values up to 6.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relative simplicity it has been widely studied both from the experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and the theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32] points of view. Because of the very small dipole moment of CO, 0.109 80D, 33 Ar-CO is a challenge both from the experimental and the theoretical points of view.…”
Section: Introductionmentioning
confidence: 99%